User-centered web development for GMI alumni website - Zakaria, N. A.; Ayu, Media Anugerah (2010)
Internet has become an influential tool to the society nowadays. In addition, the World Wide Web (WWW)technology is an appropriate partner with the internet that brings pleasant facility in order to facilitate people's daily lives. However, recent situation is changing whereby the primary concern is more on developing usable website to ensure user's satisfaction. Several researches have built website or product by employing user-centered design process to ascertain that it meets users' needs. Some of the studies also attempted in evaluating the end-product with the purpose to observe the usability. Common process in user-centered design methodology consists of requirements gathering, needs assessment, design for solution and usability assessment. This is an iterative process until the end-user satisfies with the developed product. In this study, a framework is proposed to be applied in redesigning usable GMI alumni website. Second objective of this research is to gain feedback from client and users for the purpose of web usability evaluation by using fuzzy conjoint analysis.